Optimalisasi Peran Anggota Kelompok Tani Ngodirjo I Di Desa Nyalabu Daya Kecamatan Pamekasan Kabupaten Pamekasan - Azam Azam; kustiawati ningsih; Mohammad Saedy Romli (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
This study aims to determine the performance of members of the Farmer's Group (Ngodirjo I) in Nyalabu Daya Village and to determine the strategy for improving the performance of members of the Farmer's Group (Ngodirjo I) in Nyalabu Daya Village. The research location was purposively conducted in Nyalabu Daya Village, Pamekasan District, Pamekasan Regency. The sample method used in this study is the census method in which all 30 people were interviewed in the population. The data technique was carried out in a qualitative descriptive way. The results showed that the Ngodirjo farmer group I liked to be active in activities, such as rarely holding meetings or meetings, so that it was a factor in the failure of Nyalabu Daya Village in the sector, so a strategy is needed to improve the performance of farmer groups by using a strategic approach that aims to improve the performance of farmer groups, so that the existence of farmer groups is beneficial for agricultural progress in the village, such as improving performance, using modern agricultural tools and solidifying all elements of the farming community in farming. Farmer's Group Ngodirjo I am not active in farmer group activities, in every farmer group there needs to be motivation from related parties such as